The Effectiveness of Using a Dictionary of Balaghah Terms in Improving Undergraduate Students’ Understanding of Balaghah - Mukhlisin; Syarifuddin; Miftachul Taubah (Program Studi Pendidikan Bahasa Arab Unisda Lamongan, 2026)
This study aims to examine the effectiveness of using the Dictionary of Balaghah Terms in improving students' understanding of Balaghah courses. The low understanding of abstract Arabic terminology is often a major obstacle for students in mastering this discipline. This study uses a quantitative approach with a One Group Pretest-Posttest pre-experimental design. The population as well as the sample in this study were all 5th-semester students of the Arabic Language Education Study Program at Yudharta Pasuruan University, totaling 9 students (saturated sampling). Data were collected through test instruments and analyzed using the Shapiro-Wilk normality test and Paired Sample T-Test using SPSS. The results showed a significant increase in the mean score from 53.78 at the pre-test to 89.11 at the post-test. The results of the hypothesis test showed a significance value of < 0.001 (p < 0.05), which means there is a significant influence of the use of the dictionary on students' understanding. In addition, the Cohen’s d value of 2.154 indicates a level of effectiveness in the very large (Large) category. It can be concluded that the Dictionary of Balaghah Terms is a very effective learning medium for improving students' cognitive competence in understanding Balaghah concepts deeply.